How Do Free Cash Flow and Dividend Policy Affect Stock Return? - Ningsih, L R; Soesetio, Y (KnE Social Sciences, 2018)
This research investigates the effect of free cash flow and dividend policy with various measures of stock return and announcements for three days. The use of analytical paths using SMARTPLS programme resulted in the previously hypothetical findings that the information of free cash flow stated in published financial statements is rarely used by Indonesian investors. The other result of this study showed the weakness of company governance and dividend signals.